Distinct ErbB2 receptor populations differentially interact with beta1 integrin in breast cancer cell models - Toscani, Andrés Martín (2017)
ERBB2 is a member of the ERBB family of tyrosine kinase receptors that plays a major role in breast cancer progression. Located at the plasma membrane, ERBB2 forms large clusters in spite of the presence of growth factors. Beta1 integrin, membrane receptor of extracellular matrix proteins, regulates adhesion, migration and invasiveness of breast cancer cells. Physical interaction between beta1 integrin and ERBB2 has been suggested although published data are contradictory. The aim of the present work was to study the interaction between ERBB2 and beta1 integrin in different scenarios of expression and activation. We determined that beta1 integrin and ERBB2 colocalization is dependent on the expression level of both receptors exclusively in adherent cells. In suspension cells, lack of focal adhesions leave integrins free to diffuse on the plasma membrane and interact with ERBB2 even at low expression levels of both receptors. In adherent cells, high expression of beta1 integrin leaves unbound receptors outside focal complexes that diffuse within the plasma membrane and interact with ERBB2 membrane domains. Superresolution imaging showed the existence of two distinct populations of ERBB2: a major population located in large clusters and a minor population outside these structures. Upon ERBB2 overexpression, receptors outside large clusters can freely diffuse at the membrane and interact with integrins. These results reveal how expression levels of beta1 integrin and ERBB2 determine their frequency of colocalization and show that extracellular matrix proteins shape membrane clusters distribution, regulating ERBB2 and beta1 integrin activity in breast cancer cells.